Hyperbaric oxygen therapy treatment as an alternative for a chronic sinus tract after chordoma surgery and radiation. (1st May 2022) - McCoy, Rachel; Brandon, Michelé A; Jackson, Jordan; Rubenstein, Jane; Jain, Surbhi
Abstract : Chordoma is a rare form of cancer that forms from the notochord remnants, and affects the skull and the spine. The standard treatment for a sacrococcygeal chordoma is surgery and radiation. Chordoma has a high rate of recurrence and surgery with radiation treatment can leave patients with surgical site complications, such as wounds, fistulas or sinus tracts. Repeat surgical intervention on an irradiated surgical site increases incidence of complications leading to decreased quality of life, and increased morbidity and mortality. Treatment of wound complications after surgery and high-dose radiation for a chordoma tumour is rarely reported in the literature. Herein, the author describes the case of a chronic sinus tract after surgery and radiation for a sacral chordoma tumour successfully healed by hyperbaric oxygen therapy (HBOT) in conjunction with topical antibiotics.